2022
DOI: 10.21608/ejabf.2022.254517
|View full text |Cite
|
Sign up to set email alerts
|

Site selection for fish farming using integrated GIS-spatial multi-criteria evaluation and carrying capacity approaches: case study of M'diq bay, Morocco

Abstract: Environmental protection has become one of the major concerns of the globe population. Thus, anthropic activities require the establishment and the implementation of sustainable principals and best practices' guides (UNDP, 2011; Messerli et al., 2019). Being one of the highly emerging activities with an accelerating expansion around the world over the last decades (FAO, 2020) and as an essential key to global food security (Luca & Damvakeraki, 2015; Gimpel et al., 2018), marine aquaculture has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…According to studies reviewed in this paper, it was found that 65% of papers have focused on selecting potential sites for fish farming, indicating that it is the most popular form of aquaculture. These studies have identified potential sites for a variety fish species, including Sparus aurata [22,27,28], a warm-water fish native to the Mediterranean Sea that is highly valued in the aquaculture industry due to its fast growth rate, high market demand, and adaptability to different environments. Other fish species for which potential farming sites have been identified include Rainbow trout (Oncorhynchus mykiss) [19], pangasius [15], carp [21], sturgeon [29], seabass (Dicentrarchus labrax) [22,27] and Tilapia, the latter of which has been the subject of three different studies [23,30,31].…”
Section: Classification According To Species Culturedmentioning
confidence: 99%
See 2 more Smart Citations
“…According to studies reviewed in this paper, it was found that 65% of papers have focused on selecting potential sites for fish farming, indicating that it is the most popular form of aquaculture. These studies have identified potential sites for a variety fish species, including Sparus aurata [22,27,28], a warm-water fish native to the Mediterranean Sea that is highly valued in the aquaculture industry due to its fast growth rate, high market demand, and adaptability to different environments. Other fish species for which potential farming sites have been identified include Rainbow trout (Oncorhynchus mykiss) [19], pangasius [15], carp [21], sturgeon [29], seabass (Dicentrarchus labrax) [22,27] and Tilapia, the latter of which has been the subject of three different studies [23,30,31].…”
Section: Classification According To Species Culturedmentioning
confidence: 99%
“…These studies have identified potential sites for a variety fish species, including Sparus aurata [22,27,28], a warm-water fish native to the Mediterranean Sea that is highly valued in the aquaculture industry due to its fast growth rate, high market demand, and adaptability to different environments. Other fish species for which potential farming sites have been identified include Rainbow trout (Oncorhynchus mykiss) [19], pangasius [15], carp [21], sturgeon [29], seabass (Dicentrarchus labrax) [22,27] and Tilapia, the latter of which has been the subject of three different studies [23,30,31]. Tilapia is a freshwater fish species that is widely farmed due to its fast growth rate and high adaptability.…”
Section: Classification According To Species Culturedmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish farming can contribute to the domestic output of fishery products, provide an important source of income for many smallholders, other landowners and their local communities, through their direct involvement in the value chain (production, processing, and sale), as well as offering employment opportunities [3,4]. Aquaculture and fisheries are the fastest-growing food production systems around the world and their importance for food security and global nutrition in the twenty-first century is recognized increasingly by authorities such as [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an appropriate site is fundamentally important here and adequate site selection will reduce the possible environmental impacts of the operation and the potential conflicts of this activity with the use of other resources and the sustainable development of aquaculture activities [6,7,10]. This will also guarantee an increase in economic returns [11][12][13].…”
Section: Introductionmentioning
confidence: 99%